CULTURAL INTEGRATION IN DIGITAL LEARNING: A MIXED-METHODS STUDY OF THE BANTAIAN ADAT ELECTRONIC MODULE - Ziyad Aufa; Asrial Asrial; Muhammad Sofwan (Universitas Islam Negeri Mataram, 2025)
This study aims to analyze the integration of Bantaian Adat local wisdom into the teaching of Integrated Science and Social Studies (IPAS) through the use of an electronic module in elementary schools. The research employed a mixed methods approach with a sequential explanatory design, combining quantitative and qualitative approaches in successive stages. The study involved 40 fourth grade students from classes IVA and IVB, as well as two fourth grade teachers one from the experimental class and one from the control class who participated in interviews. Quantitative data were collected through pre tests and post tests to measure the improvement in students’ learning outcomes after using the Bantaian Adat based electronic module. The results indicated a significant improvement, with an average pre test score of 68.25 and a post test score of 85.40, yielding an N gain of 0.54 (moderate category). Qualitative data were obtained through in depth interviews and classroom observations in both groups, showing that the teacher in the experimental class perceived an increase in student engagement and greater ease in connecting local values with scientific and social concepts. This study emphasizes that the integration of Bantaian Adat local wisdom through an electronic module not only enhances students’ learning outcomes but also strengthens their character and cultural identity in IPAS learning at the elementary school level.